Crop Combination Region of Ausgram Gram Panchayet in West Bengal, India (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper is analysed the crop combination region in Ausgram Gram Panchayet of Purba Bardhaman District in West Bengal. Bardhaman district is known as „Dhaner Gola‟ of West Bengal. There are 11 villages of our study area of Ausgram Gram Panchayat. These are Ausgram, Ausgram chak, Alefnagar, Bannabagram, Bahamanpur, Barchatra, Karatia, Kunjanagar, Purbatati, Ramchandrapur and Warishpur. Agriculture is the dominant economic activity of the study area. Rice, Potato, Mustard, Til, Wheat, Jute, Sugarcane are the main crops cultivated in the study area. The ranking of crops analysis by J.C. Weaver‟s(1954) minimum deviation method. There are three cropping seasons in the study region, namely Kharif, Rabbi and summer. During 2014-2015 monocrop combination present in only Ausgram chak while two crop combinations present in Kunjanagar and Warishpur where as Three crop combination was found in Ausgram and Bahamanpur, while four crops combination found in Barchatra and Purbatati , five crop combination was found in Alefnagar, Bannabagram, Ramchandrapur and Karatia was found six crop combination during study period.